Two three-dimensional [MoIII(CN)7]4−-based magnets showing new topologies and ferrimagnetic ordering below 80 K. Issue 24 (29th May 2019) - Wei, Xiao-Qin; Wang, Kang-Jie; Wu, Dong-Qing; Shao, Dong; Shi, Le; Shen, Fu-Xing; Wei, Hai-Yan; Wang, Xin-Yi
Abstract : Two 3D [Mo III (CN)7 ] 4− -based magnets with new topologies and ferrimagnetic ordering below 80 K have been prepared using different amides as auxiliary ligands. Abstract : The rational design and synthesis of heptacyanomolybdate-based magnets remain a challenge due to the complexity of this system. Here, we reported the crystal structures and magnetic properties of two three-dimensional (3D) frameworks prepared from the self-assembly of the [Mo III (CN)7 ] 4− unit with Mn II ions in the presence of different amide ligands, namely Mn2 (DMF)(H2 O)2 [Mo(CN)7 ]·H2 O·CH3 OH (1 ) and Mn2 (DEF)(H2 O)[Mo(CN)7 ] (2 ) (DMF = N, N ′-dimethylformamide and DEF = N, N ′-diethylformamide). Single-crystal structure determinations showed that compound1 crystallizes in the triclinic space group P ī, while2 crystallizes in the monoclinic space group P 21 / n . The difference in the structures of1 and2 is the coordination mode of the amide molecules: while the DMF molecules in1 are only terminal ligands, the DEF molecules in2 act as bridging ligands between two Mn II centers. Although their space groups and local coordination environments of the metal centers are of some difference, both compounds have similar extended 3D frameworks where the spin centers are bridged by both the CN − and μ2 -O bridges. They both have a three-nodal 4, 4, 7-connecting topological net with the vertex symbol of {4 3 ·5 3 }{4 4 ·5 2 }{4 7 ·5 4 ·6 6 ·7 4 } for1, and {4 3 ·5 3 }{4 4 ·5 2 }{4 7 ·5 4 ·6 7 ·7 3 } for2, respectively. Magnetic measurements revealed that both1 and2 exhibit ferrimagnetic ordering below 80 K together with another anomaly at about 45 K probably owing to spin reorientation. Besides, spin frustration and non-linear alignment of the magnetic moments are also possible due to competitive antiferromagnetic interactions between the spin carriers. These compounds expanded the family of Mn II –[Mo III (CN)7 ] 4− magnets with high magnetic ordering temperatures.